Performance Attribution using the Brinson model: Evidence from Finnish Institutional Investors - Komppula, Anu (My University, 2016)
The main purpose of this study is to examine how well the Finnish institutional investors have been able to perform. Hypotheses propose that Finnish institutional investors have been able to achieve excess return in relation to their benchmark, and that asset allocation has been the main cause for the excess return. The data for the study is provided by Investment Research Finland Ltd. The company is the leading provider of investment portfolio performance measurement and consolidated reporting services for Finnish institutional investors. Data is transactions based data and consists of daily returns for 24 institutional investors and benchmarks for their portfolios between 31.12.2011-31.12.2015. The Brinson model is used to calculate performance attribution on all investments, equities and fixed income, as well as the sector level results. The results contradict with some of the earlier studies on performance attribution. The results imply that Finnish institutional investors have not been able to achieve excess return. Asset allocation, although more positive than selection effect, could not be seen as the main effect on portfolio performance. The study also finds that there are significant differences between equities and fixed income. Equities had a more positive contribution to total attribution results than fixed income. The results also indicate that the Brinson model may not be a suitable model for calculating fixed income performance attribution, as also criticized by previous researchers.
Keywords: Performance attribution; Brinson model; portfolio analysis; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Master's Degree Programme in Finance|